KEPUASAN WARGA BELAJAR, BELAJAR DI PKBM INSAN CENDEKIA KELURAHAN SIALANG MUNGGU KECAMATAN TAMPAN KOTA PEKANBARU - Azzahrah, Putri Azizah; Wilson, Wilson; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the Satisfaction of the Students of Learning, Learning in PKBM Insan Cendekia Sialang Munggu Kecamatan Tampan Pekanbaru City. The formulation of the problem of this research is the Satisfaction of the Students of Learning, Learning in PKBM Insan Cendekia Sialang Munggu Kecamatan Tampan Pekanbaru City is high. The population in this study as many as 43 residents learn. the researchers used a saturated sample so that all the population in the sample as much as 43 residents studying in PKBM Insan Cendekia Sialang Munggu Kecamatan Tampan Pekanbaru City, and 20 people for trials in Learning Activity Center (SKB) Pekanbaru City. The type of this research is descriptive with quantitative approach. The data collection instrument is a questionnaire with 40 statements and after the trial live 37 valid statements to be made in the research instrument. Data analysis through quantitative descriptive analysis. The findings of this study indicate that the satisfaction of studying residents, learning in PKBM Insan Cendekia Sialang Munggu Kecamatan Tampan Kota Pekanbaru the highest learning service by tutor with percentage 64,92% means that tutor provide good service to citizen learn in learning activity. Keywords: Satisfaction, Learning, Equality.